Engineering skyrmion and helical states in FeGe nanocylinders through angular field control - Escrig-Murua, J; Saavedra-Díaz, E (ELSEVIER, 2026)
We investigate how the orientation of an external magnetic field influences magnetization reversal and spin textures in FeGe nanocylinders using micromagnetic simulations based on the Landau-Lifshitz-Gilbert equation in MuMax3. FeGe, a prototypical chiral magnet with Dzyaloshinskii-Moriya interaction (DMI), stabilizes nontrivial spin textures such as skyrmions. We analyze nanocylinders of fixed length (50 nm) and diameters of 50-100 nm, subjected to fields applied at angles from 1 degrees to 91 degrees relative to the cylinder axis. Results show a pronounced angular dependence of coercivity and remanence, with sharp drops at diameter-dependent critical angles marking transitions from skyrmion-mediated reversal to trivial helical modes. Topological charge analysis confirms that below the critical angle, slices exhibit values near unity, while above it, the topological character vanishes. For larger diameters (90-100 nm), S-shaped helices linked to remanence minima emerge. These findings highlight angular control as a design parameter in spintronic devices exploiting topological textures.
Keywords: FeGe nanocylinders; Micromagnetic simulations; Angular field control; Topological charge; Spintronics